Enhancing IoT Network Security Through Digital Object Architecture-Based Approaches - Mahmood Al-Bahri; Wasin Alkishri; Falah Y. H. Ahmed; Marwan Alshar'e; Sanad Al Maskari (Qubahan Academic Journal)
The Internet of Things (IoT) encompasses a network of different devices, both stationary and mobile, that may interact with the physical world. Ensuring the security of the Internet of Things (IoT) is of utmost importance in a world where devices are interconnected at various levels, including wearables, home automation, smart cities, industrial sectors, and more. Ensuring the security of this interconnected network of "things" and devices is imperative, leaving no space for mistakes or inadequacies. The purpose of this article is to present an approach that utilizes Digital Object Architecture (DOA) to identify Internet of Things (IoT) devices and applications within communication networks. This study investigates various methodologies for incorporating the DOA identifier into Internet of Things (IoT) devices that are equipped with a range of wireless data transmission modules. Furthermore, this study presents a security model that aims to strengthen the resolution system based on data transmission security. The objective is to reduce the number of service messages exchanged between internetwork parts and decrease network latency. The essay finishes by examining some strategies for modernizing DOA in order to improve the quality of service.